Generation of an NFκB-Driven Alpharetroviral “All-in-One” Vector Construct as a Potent Tool for CAR NK Cell Therapy - Rudek, Loreen Sophie; Zimmermann, Katharina; Galla, Melanie; Meyer, Johann; Kuehle, Johannes; Stamopoulou, Andriana; Brand, Daniel; Sandalcioglu, I. Erol; Neyazi, Belal; Moritz, Thomas; Rossig, Claudia; Altvater, Bianca; et al. (Frontiers in Immunology, 2021)
Immune cell therapeutics are increasingly applied in oncology. Especially chimeric antigen receptor (CAR) T cells are successfully used to treat several B cell malignancies. Efforts to engineer CAR T cells for improved activity against solid tumors include co-delivery of pro-inflammatory cytokines in addition to CARs, either via constitutive cytokine expression or inducible cytokine expression triggered by CAR recognition of its target antigen – so-called “T cells redirected for universal cytokine-mediated killing” (TRUCKs) or 4th generation CARs. Here, we tested the hypothesis that TRUCK principles could be expanded to improve anti-cancer functions of NK cells. Comparison of the functionality of inducible promoters responsive to NFAT or NFκB in NK cells showed that, in contrast to T cells, the inclusion of NFκB-responsive elements within the inducible promoter construct was essential for CAR-inducible expression of the transgene. We demonstrated that GD2CAR-specific activation induced a tight NFκB-promoter-driven cytokine release in NK-92 and primary NK cells together with an enhanced cytotoxic capacity against GD2+ target cells also shown by increased secretion of cytolytic cytokines. The data demonstrate biologically relevant differences between T and NK cells that are important when clinically translating the TRUCK concept to NK cells for the treatment of solid malignancies.